Resource materials in air and water pollution control for college classes in chemical technology - Maglinao, Raphia Binudin (1976)
This paper attempts to provide a resource material for the teaching of CHET 311 which was offered beginning the first semester of school year 1977-1978. To suit the need of technicians, it is necessary that the teaching approach for pollution study must be laboratory-oriented and conceptual to develop practical as well as theoretical skills. The resource material is composed of three components, namely: a course outline for teaching Air and Water Pollution control, five sample teaching lessons with tried-out experiments, and a content background on basic concepts on environmental pollution.